Modelling of melting in packed media due to forced air convection with higher temperature using Euler-Euler-Lagrangian approach - Soon, Genevieve (2022)
The formulation of the CFD-DEM method, CD-MELT, is further extended to three phases (gas, liquid and solid) with melting in this study. The new CD-MELT provides the characterizations of the three individual phases, which is superior to the current VOF approaches whereby the fluid phases (gas and liquid) are lumped together in the computational cell and not distinguished. In addition, CD-MELT allows for the consideration of both latent heat and sensible heat in the non-isothermal melting process via the introduction of a particle enthalpy variable, where the melting rate is determined by the balance of heat gained from convection and heat required for melting. To demonstrate the new capability, CD-MELT is applied to simulate the non-isothermal melting of wax spheres packed in a single layer in a glass bed subjected to forced air convection with higher temperature, where the setting is similar to an earlier experimental study. In this application, the coarse graining approach is adopted to simplify the modelling of the melting rate and bed packing, based on theoretical considerations of the source terms and variables for non-isothermal melting. The predictions of CD-MELT are then compared with the published experimental and theoretical studies related to this application. It is found that latent heat and most importantly tracking of the melted liquid phase are dominant factors in order to simulate the melting process accurately. Furthermore, the predictions on the melted liquid movement through the packed bed by CD-MELT provides additional insights to the gas channel formations and liquid holdup phenomena which cannot be obtained using the VOF approach.